Studi Ekperimental Penambahan Reflektor Datar Pada Kompor Tenaga Surya Tipe Parabolic - Mardwianta, Benedictus; Subarjo, Abdul Haris; Cahyadi, Rivaldi Dwi (JURNAL SURYA ENERGY, 2021)
Community needs to meet electrical energy are increasing. This increasing need has not been matched by the supply of energy. Currently, the main supply of energy comes from non-renewable fossils. To maintain energy reselliance, it is necessary to find alternative energy sources, one of which comes from solar energy. In this research, a parabolic solar cooker was made using autodesk and then tested the prototype solar cooker without additional mirrors, one additional mirror, and two mirrors. At the end of the study an analysis was carried out. The energy efficiency results obtained on a parabolic type solar stove without the addition of a flat mirror is 3.19% with an average stove power of 22.33 watts. The energy efficiency obtained on a parabolic type solar stove with the addition of two flat mirrors is 4.87% with an average stove power of 26.01 watts.